The Internal Generation of the Atlantic Ocean Interdecadal Variability - Arzel, Olivier; Huck, Thierry; Colin De Verdiere, Alain (Journal of Climate, 2018)
Numerical simulations of a realistic ocean general circulation model forced by prescribed surface fluxes are used to study the origin and structure of intrinsic interdecadal variability of the ocean circulation. When eddy-induced turbulent diffusivities are low enough, spontaneous oscillations of the Atlantic meridional overturning circulation (AMOC) with periods O(20) yr and amplitude O(1) Sv (1 Sv ≡ 106 m3 s−1) emerge. The transition from the steady to the oscillatory regime is shown to be consistent with a supercritical Hopf bifurcation of the horizontal Peclet number. Adding atmospheric thermal damping is shown to have a very limited influence on the domain of existence of intrinsic variability. The spatial structure of the mode consists of a dipole of sea surface temperature (SST)/sea surface height (SSH) anomalies centered at about 50°N with stronger variance in the western part of the subpolar gyre, in agreement with the observed Atlantic multidecadal oscillation (AMO) signature in this region. Specific features include a westward propagation of temperature anomalies from the source region located on the western flank of the North Atlantic Current (NAC) and a one-quarter phase lag between surface and subsurface (800 m) temperature anomalies. Local linear stability calculations including viscous and diffusive effects confirm that the North Atlantic Current is baroclinically unstable on scales of O(1000) km with growth rates of O(1) yr−1. Both the spatial structure of the mode and the period agree in magnitude with in situ measurements in the North Atlantic, suggesting that this intrinsic ocean mode participates in the observed Atlantic bidecadal climate variability.